2011
DOI: 10.1007/s10695-011-9474-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory volume response following hypotonic stress in Atlantic salmon erythrocytes

Abstract: The purpose of this study was to examine regulatory volume decrease (RVD) in Atlantic salmon red blood cells (RBCs). Osmotic fragility was determined optically, mean cell volume was measured electronically, and changes in intracellular Ca(2+) concentration were visualized using fluorescence microscopy and fluo-4-AM. Cells displayed an increase in osmotic fragility and an inhibition of volume recovery following hypotonic shock when they were exposed to a high taurine Ringer or when placed in a high K(+) medium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Changes in macromolecular density are intimately linked to cell volume changes. Experiments with primary fish cells isolated from a wide variety of tissues have shown an abundance of molecular responses to osmotically induced changes in cell volume, and the corresponding literature is too extensive to be reviewed here (6,16,40,73,88,107,108,178,193). Some of these studies imply that membrane stretch is a trigger for osmosensory signal transduction.…”
Section: The Role Of Macromolecular Crowding and Damage For Osmosensingmentioning
confidence: 99%
“…Changes in macromolecular density are intimately linked to cell volume changes. Experiments with primary fish cells isolated from a wide variety of tissues have shown an abundance of molecular responses to osmotically induced changes in cell volume, and the corresponding literature is too extensive to be reviewed here (6,16,40,73,88,107,108,178,193). Some of these studies imply that membrane stretch is a trigger for osmosensory signal transduction.…”
Section: The Role Of Macromolecular Crowding and Damage For Osmosensingmentioning
confidence: 99%
“…This homeostatic response has been mostly investigated in mammalian cells but also in cells of lower vertebrates and invertebrates. Cell volume regulation has been observed in numerous cell types, such as astrocytes [5], erythrocytes from different sources [6,7], lymphocytes [8] and sperm [9]. RVD was also studied in invertebrate cells [10][11][12][13][14][15][16], although details of its mechanisms are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the sources of [Ca 2+ ] i transients observed during the RVD and the RVI processes are different and the possible link between [Ca 2+ ] i increase and the RVI process has not been elucidated (Marino & La Spada, ; Wormser et al . ). Some studies have indicated that the [Ca 2+ ] i increase in response to hyperosmolarity is due to NKCC1 activity, which allows membrane depolarization (van Mil et al .…”
Section: Discussionmentioning
confidence: 97%